2022
DOI: 10.1136/bmjopen-2021-056517
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic review and meta-analysis to examine intrapartum interventions, and maternal and neonatal outcomes following immersion in water during labour and waterbirth

Abstract: ObjectivesWater immersion during labour using a birth pool to achieve relaxation and pain relief during the first and possibly part of the second stage of labour is an increasingly popular care option in several countries. It is used particularly by healthy women who experience a straightforward pregnancy, labour spontaneously at term gestation and plan to give birth in a midwifery led care setting. More women are also choosing to give birth in water. There is debate about the safety of intrapartum water immer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 80 publications
1
15
1
Order By: Relevance
“…These findings are similar to the results of the studies by Gautham and Devi (2020) and Zhang and Yang (2022). Contrary to our study, two studies found that water immersion was effective in reducing postpartum haemorrhage (Burns et al, 2022; Cristina et al, 2022). That these results did not indicate that hydrotherapy had a negative effect on postpartum haemorrhage, considered a major cause of maternal death, implies that the practice can be used as a safe option in intrapartum care.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…These findings are similar to the results of the studies by Gautham and Devi (2020) and Zhang and Yang (2022). Contrary to our study, two studies found that water immersion was effective in reducing postpartum haemorrhage (Burns et al, 2022; Cristina et al, 2022). That these results did not indicate that hydrotherapy had a negative effect on postpartum haemorrhage, considered a major cause of maternal death, implies that the practice can be used as a safe option in intrapartum care.…”
Section: Discussioncontrasting
confidence: 99%
“…This study showed that the use of hydrotherapy in the first stage of labour effectively reduces the intensity of pain. Similar results were reported in previous studies (Burns et al, 2022; Cluett et al, 2018; Cowan et al, 2017). It has been asserted in the literature that by reducing the level of vasopression, hydrotherapy increases uterine perfusion, thereby facilitating neurohormonal interactions and resulting in less pain (Henrique et al, 2018; Mascarenhas et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations